Teaching English for students with special needs requires supportive and adaptive instructional strategies that consider learners’ emotional and cognitive conditions. In special education contexts, conventional teaching approaches often limit student engagement and learning comfort. This study aimed to explore the use of Quizizz as a supportive digital strategy in teaching English for students with special needs.This research employed a qualitative descriptive approach. The study was conducted i - Rinda Rinda (JETS, English Department of University of Uluwiyah Mojokerto, 2023)
Teaching English for students with special needs requires supportive and adaptive instructional strategies that consider learners’ emotional and cognitive conditions. In special education contexts, conventional teaching approaches often limit student engagement and learning comfort. This study aimed to explore the use of Quizizz as a supportive digital strategy in teaching English for students with special needs. This research employed a qualitative descriptive approach. The study was conducted in a special school involving students with special needs and an English teacher. Data were collected through classroom observations, documentation, and teacher reflections during the implementation of Quizizz in English learning activities. The data were analyzed qualitatively to identify patterns related to student engagement, learning comfort, and instructional adaptation. The findings show that the use of Quizizz created a more supportive and engaging learning atmosphere. Students demonstrated higher participation and enthusiasm during English lessons, while the interactive features of Quizizz helped reduce learning anxiety. In addition, Quizizz allowed the teacher to adjust instructional strategies according to students’ abilities, supporting inclusive and student-centered learning. Therefore, Quizizz can be considered an effective supportive digital strategy in teaching English for students with special needs.